2002
DOI: 10.1097/00000478-200204000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Solid Variant of Mammary Adenoid Cystic Carcinoma With Basaloid Features

Abstract: Adenoid cystic carcinoma of the breast is a rare neoplasm that represents <1% of breast carcinomas. The tumors are histologically indistinguishable from examples in other sites, and they have a generally favorable prognosis. Several studies have investigated the possible correlation between histologic grade in adenoid cystic carcinoma (largely determined by cytology and growth pattern) and prognosis. Some earlier reports concluded that a solid variant of mammary adenoid cystic carcinoma had a more aggressive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
115
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(129 citation statements)
references
References 24 publications
12
115
0
2
Order By: Relevance
“…By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells. However, even by using a double immunostaining procedure, we were unable to identify a CK5/6 þ /P63 þ population of cells which could correspond to myoepithelial precursor cells.…”
Section: Discussionsupporting
confidence: 84%
“…By classifying breast cell populations according to the system proposed by Bocker, 36 we identified four distinct types of cells in adenoid cystic carcinoma of the breast; rare CK5/6 þ cells (CK8/18À/p63À) or progenitor cells, CK5/6 þ /CK8/18 þ cells (/p63À) or glandular precursor cells, CK8/18 þ cells Although the origin of adenoid cystic carcinoma of the breast is still debated, it seems to be widely accepted that this tumor is derived from undifferentiated cells, which have the capacity to differentiate towards ductal and myoepithelial cells. 9,10,25,37 Our study confirmed this theory, as we demonstrated the presence of CK5/6 þ cells that could represent precursor cells. However, even by using a double immunostaining procedure, we were unable to identify a CK5/6 þ /P63 þ population of cells which could correspond to myoepithelial precursor cells.…”
Section: Discussionsupporting
confidence: 84%
“…[1][2][3] The constituent neoplastic cells are both of luminal and myoepithelial type, arranged in a wide spectrum of histological patterns, that is, trabecular, tubular-cribriform, solid, and basaloid, which usually coexist in the same tumor. [1][2][3][4][5][6][7] Most adenoid cystic carcinomas follow a favorable clinical course with a low prevalence of axillary lymph node metastases (approximately 10%). Tumors showing a predominant solid pattern of growth however reportedly have a more aggressive behavior, 8 with distant metastases despite the absence of lymph node involvement and poor 5-year overall survival.…”
mentioning
confidence: 99%
“…Tumors showing a predominant solid pattern of growth however reportedly have a more aggressive behavior, 8 with distant metastases despite the absence of lymph node involvement and poor 5-year overall survival. 6,[9][10][11][12][13] Adenoid cystic carcinoma, especially when showing a predominant tubular-cribriform growth pattern, shares many histological features with infiltrating cribriform and tubular carcinoma. These are more commonly encountered special types of breast cancer, characterized by a long-term survival in more than 80% of the cases.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ACC developing in the salivary glands is reported to exhibit a better prognosis than other pathological types of carcinoma occurring in the salivary glands, due to its slow growth and absence of metastasis until the late stages of tumor development [8]. Shin et al [9] reported that breast ACCs follow a favorable clinical course, with a better prognosis than that of salivary disease, while Cerar et al reported that esophageal ACCs have a worse prognosis due to their vital location and the development of synchronous tumors of the esophagus [10]. ACC has a distinctive microscopic appearance, and its histological features are useful not only in diagnosing the tumor but also help to determine the prognosis.…”
Section: Discussionmentioning
confidence: 99%